Determinants Of Treatment Adherence In Drug-Sensitive Tuberculosis Patients During The Covid-19 Pandemic - Easter Adhi Astuti; Ayun Sriatmi; Wulan Kusumastuti (Poltekkes Kemenkes Surakarta, 2022)
Background: During the COVID-19 pandemic in Surakarta, there were patients who were absent, failed, and dropped out of treatment. This study aims to analyze factors associated with treatment adherence of drug-sensitive tuberculosis patients (TB-SO) during the COVID-19 pandemic at the Surakarta City Public Health Center. Methods: This research method combines quantitative research with cross-sectional research. A sample of 105 patients from 10 Public Health Center (Puskesmas) in Surakarta City was obtained using a total population sampling based on inclusion and exclusion criteria. This research was conducted from April to June 2022. The research instrument used was a questionnaire, and the data was analyzed univariate and bivariate with the chi-square. Results: This study showed that more patients were adherere (79%) than non-adherent (21%). Factors related to treatment adherence were the role of health professionals (p = 0.045) and Treatment Supervisors (Pengawas Menelan Obat/PMO) support (p = 0.035). Conclusion: The role of health workers and the support provided by the PMO to patients related to adherence to treatment for TB-SO patients Therefore, it is expected that health professionals need to keep a good relationship with patients through personal counseling and need to provide socialization to PMOs.